2010
DOI: 10.1111/j.1463-6395.2009.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and ultrastructural studies of male reproductive tract and spermatozoa in Xylocopa frontalis (Hymenoptera, Apidae)

Abstract: Fiorillo, B. S., Zama, U., Lino-Neto, J. and Báo, S. N. 2010. Structural and ultrastructural studies of male reproductive tract and spermatozoa in Xylocopa frontalis (Hymenoptera, Apidae). -Acta Zoologica (Stockholm) 91: 176-183.In Xylocopa frontalis the reproductive tract is composed of testes, deferent ducts, seminal vesicles, accessory glands and an ejaculatory duct. Each testis comprises four testicular tubules in which multiple cysts are present containing approximately 64 spermatozoa per cyst. The semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Morphological aspects of the male reproductive system of parasitoids analyzed are similar to those described for most Hymenoptera (Dallacqua and Cruz-Landim, 2003;Ferreira et al, 2004;Damiens and Boivin, 2005;Araú jo et al, 2005a;Brito et al, 2005;Bushrow et al, 2006;Fiorillo et al, 2008Fiorillo et al, , 2009). However, the number of follicles per testis varies considerably between the different groups.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Morphological aspects of the male reproductive system of parasitoids analyzed are similar to those described for most Hymenoptera (Dallacqua and Cruz-Landim, 2003;Ferreira et al, 2004;Damiens and Boivin, 2005;Araú jo et al, 2005a;Brito et al, 2005;Bushrow et al, 2006;Fiorillo et al, 2008Fiorillo et al, , 2009). However, the number of follicles per testis varies considerably between the different groups.…”
Section: Discussionmentioning
confidence: 90%
“…All studied species of Hymenoptera which have been morphological and which had their reproductive system characterized showed a dilated and modified region in the deferent ducts specialized for the storage of spermatozoa-a seminal vesicle (Dallacqua and Cruz-Landim, 2003;Ferreira et al, 2004;Damiens and Boivin, 2005;Araú jo et al, 2005a;Brito et al, 2005;Bushrow et al, 2006;Lima et al, 2006;Fiorillo et al, 2009). In some Chalcidoidea it is formed of two distinct morphological portions (Gerling and Legner, 1968;Damiens and Boivin, 2005;Fiorillo et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…In Scelionidae, only one mitochondrial derivative was observed, extending to the anterior extremity of the nucleus (Lino-Neto and Dolder, 2001a). The termination of the mitochondrial derivatives in the final portion of the flagellum in D. connubialis is similar to that observed in most Aculeata Apidae (Zama et al, 2001(Zama et al, , 2004(Zama et al, , 2005aFiorillo et al, 2005Fiorillo et al, , 2009Gracielle et al, 2009), Sphecidae (Zama et al, 2005b) and Vespidae (Mancini et al, 2006(Mancini et al, , 2009, in which one mitochondrial derivative terminates before the other, but differs from P. nasuta, in which the two mitochondrial derivatives terminate together (Oliveira et al, 2010).…”
Section: Discussionmentioning
confidence: 64%
“…Many similar morphological characteristics associated with the male reproductive system were found in comparative studies on the Hymenoptera (Araú jo et al., 2005a,b, 2009Brito et al, 2005;Bushrow et al, 2006;Dallacqua and Cruz-Landim, 2003;Damiens and Boivin, 2005;Ferreira et al, 2004;Fiorillo et al, 2008Fiorillo et al, , 2009Moreira et al, 2008Moreira et al, , 2010. On the other hand, these studies also identified several features that differed between the various groups.…”
Section: Discussionmentioning
confidence: 79%